DIALECTICS OF WOMEN DOMESTICATION IN QS. AL-AḤZĀB VERSE 33 FROM THE PERSPECTIVE OF ĀBID AL-JĀBIRī'S HERMENEUTICS - Walkaromah, Naylul ‘Izzah; Safdhinar Muhammad An Noor (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2023)
The dichotomy of opinions on women's work in the public and domestic spheres and the gender equality discourse have become interesting issues in Islamic studies. In addressing the activities and roles of women, some groups make al-Aḥzāb verse 33 the basis for women's obligation to stay at home and prohibit them from participating in activities in the public domain. This qualitative library research employs the hermeneutic approach. It aims to obtain the contextual meaning in al-Aḥzāb verse 33 through the theory of Quranic hermeneutics developed by a Muslim intellectual, Ābid al-Jābirī. The hermeneutics promoted by al-Jabiri aim to make the moral values contained in the Qur'an be implied in the fabric of society and harmony with the current context. To obtain an objective and comprehensive interpretation of a text, al-Jabiri takes two steps. The first step is to explore the concept of al-faṣl and the second is to explore the concept of al-waṣl. The results suggest that women are free to partake in the public sphere within certain restrictions specified by Islamic law. However, women's activities in the public sphere should not be an excuse to neglect their role in the domestic sphere.